The renaissance of emotion : understanding affect in Shakespeare and his contemporaries - Meek, Richard, 1975-; Sullivan, Erin (Cultural historian) (Manchester Shakespeare collection, 2015)
This collection of essays offers a major reassessment of the meaning and significance of emotional experience in the work of Shakespeare and his contemporaries. Recent scholarship on early modern emotion has relied on a medical-historical approach, resulting in a picture of emotional experience that stresses the dominance of the material, humoral body. The Renaissance of emotion seeks to redress this balance by examining the ways in which early modern texts explore emotional experience from perspectives other than humoral medicine. The chapters in the book seek to demonstrate how open, creative and agency-ridden the experience and interpretation of emotion could be. Taken individually, the chapters offer much-needed investigations into previously overlooked areas of emotional experience and signification; taken together, they offer a thorough re-evaluation of the cultural priorities and phenomenological principles that shaped the understanding of the emotive self in the early modern period. The Renaissance of emotion will be of particular interest to students and scholars of Shakespeare and Renaissance literature, the history of emotion, theatre and cultural history, and the history of ideas.